Confixal adverbs of adverbial meaning in the Ukrainian language of the second part of the 19 century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the adverbs of adverbial meaning. formed with the help of confixes, the morphological ways of adverb formation are analysed, productive and non-productive adverbial models are considered.
Keywords: adverbial word-formation; derivational system; confixal models